MORPHOMETRIC CHARACTERISTICS OF GINGIVAL COMPONENTS AT DIFFERENT TERMS OF EXPERIMENTAL OPIOID INFLUENCE - Fik V. B.; Palʹtov Ye. V. (World Science, 2020)
The aim of the study was to investigate changes in morphometric parameters of the gingival epithelial thickness, connective tissue papillae height and lumen diameter of arterioles, capillaries and venules in the dynamics after two, four and six weeks of experimental opioid exposure. Studies were performed on outbred white male rats. In the experiment, animals were injected with increasing opioid analgesic nalbuphine for six weeks, which ranged from 0.212 to 0.252 mg / kg. For histological and morphometric studies, semi-thin sections of the upper and lower jaws of rats were used. It was found that with the introduction of the opioid analgesic nalbuphine in increasing doses, the difference in the components of the periodontium were statistically significant compared with similar values of intact animals, indicating reactive changes in the gingival mucosa during short-term opioid action. After six weeks of opioid exposure, morphometrically revealed a sharp change in the vector of dynamics, which was manifested by statistically significant changes in the values of the components of the gums compared with similar indicators of intact animals, indicating the development of inflammatory- dystrophic changes in periodontal tissues.